2009
DOI: 10.1098/rspb.2008.1958
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk increases with natal dispersal distance in American martens

Abstract: The assumption that mortality risk increases with dispersal distance has rarely been tested. We compared patterns of natal dispersal in the American marten (Martes americana) between a large regenerating forest landscape and an uncut landscape that was dominated by more mature forest to test whether mortality risk increased with dispersal distance, and whether variation in mortality risk influenced dispersal distance. Mortality risk increased with dispersal distance in both landscape treatments, but the distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 31 publications
(69 reference statements)
5
81
0
Order By: Relevance
“…In addition, movement responses to habitat clustering may depend on whether movements are biased towards specific directions 90 (e.g.habitat) (Farnsworth and Beecham 1999). This is an important problem in landscape ecology because the fitness consequences of large dispersal distancesare different from the fitness consequences of small dispersal distances (Johnson et al 2009),with potential repercussions for the evolution of dispersal (Travis 2001). …”
mentioning
confidence: 99%
“…In addition, movement responses to habitat clustering may depend on whether movements are biased towards specific directions 90 (e.g.habitat) (Farnsworth and Beecham 1999). This is an important problem in landscape ecology because the fitness consequences of large dispersal distancesare different from the fitness consequences of small dispersal distances (Johnson et al 2009),with potential repercussions for the evolution of dispersal (Travis 2001). …”
mentioning
confidence: 99%
“…Specifically, Chapin et al (1998) observed that non-resident martens selected much smaller patches of residual forest (>6 m in height) than resident martens, and Payer and Harrison (1999) found a similar but weaker relationship in home range-scale habitat selection between yearling and mature martens. If traplines with little suitable habitat were acting as sinks for juvenile animals, poor body condition (as observed by Johnson et al 2009) and increased vulnerability to trapping may have further undermined the relationship between trapper success and habitat quality. Repeating the current analyses using the number of adult martens trapped, or the ratio of juvenile to adult martens, as the dependent variable may result in a stronger association between trapper success and the quantity and spatial configuration of suitable habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The traplines in our study were large (average of 160 km 2 to 190 km 2 ), suggesting that the number of juvenile martens trapped on a trapline should reflect recruitment on that trapline. However, given that average juvenile marten dispersal distances range from 4 km to 18 km (Broquet et al 2006a, Johnson et al 2009, it is plausible that on some traplines a significant proportion of harvested martens may have immigrated from adjacent areas, or still be in the process of dispersing (Johnson 2008). If resident or dispersing juvenile martens occupy traplines with lower-quality habitat than their adult counterparts, we would expect results similar to what we observed-only a weak relationship between the quantity and spatial configuration of suitable habitat and trapper success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pine martens show strong territoriality, resulting in large home ranges and high dispersal of, at least in the Netherlands , especially the juvenile males. Natal dispersal distances of up to 9 km in females and up to 181 km in males were reported for the related American marten (Martes americana; Johnson et al 2009), suggesting that occasional dispersal over [100 km may also occur in pine martens.…”
Section: Introductionmentioning
confidence: 99%